Reducement of cadmium adsorption on clay minerals by the presence of dissolved organic matter from animal manure - Zhou, Wenjun; Ren, Lingwei; Zhu, Lizhong (Environmental pollution (1987), 2017)
Clay minerals are the most popular adsorbents/amendments for immobilizing heavy metals in contaminated soils, but the dissolved organic matter (DOM) in soil environment would potentially affect the adsorption/immobilization capacity of clay minerals for heavy metals. In this study, the effects of DOM derived from chicken manure (CM) on the adsorption of cadmium (Cd2+) on two clay minerals, bentonite and zeolite, were investigated. The equilibrium data for Cd2+ sorption in the absence or presence of CM-DOM could be well-fitted to the Langmuir equation (R2 > 0.97). The presence of CM-DOM in the aqueous solution was found to greatly reduce the adsorption capacity of both minerals for Cd2+, in particular zeolite, and the percentage decreases for Cd2+ sorption increased with increasing concentrations of Cd2+ as well as CM-DOM in aqueous solutions. The adsorption of CM-DOM on zeolite was greater than that on bentonite in the absence of Cd2+, however, a sharp increase was observed for CM-DOM sorption on bentonite with increasing Cd2+ concentrations but little change for that on zeolite, which can be attributed to the different ternary structures on mineral surface. The CM-DOM modified clay minerals were utilized to investigate the effect of mineral-adsorbed CM-DOM on Cd2+ sorption. The adsorbed form was found to inhibit Cd2+ sorption, and further calculation suggested it primarily responsible for the overall decrease in Cd2+ sorption on clay minerals in the presence of CM-DOM in aqueous solutions. An investigation for the mineral surface morphology suggested that the mineral-adsorbed CM-DOM decreased Cd2+ sorption on bentonite mainly through barrier effect, while in the case of zeolite, it was the combination of active sites occupation and barrier effect. These results can serve as a guide for evaluating the performance of clay minerals in immobilizing heavy metals when animal manure is present in contaminated soils. [Display omitted] •The presence of CM-DOM greatly reduces Cd2+ sorption on bentonite and zeolite.•The presence of Cd2+ significantly promotes CM-DOM sorption on bentonite.•The two clay mineral/CM-DOM/Cd2+ systems exhibit different ternary structures.•The decrease in Cd2+ sorption is mainly attributable to mineral-adsorbed CM-DOM.•Decrease mechanisms for bentonite and zeolite are discussed based on SEM study. The dissolved organic matter from animal manure has potential negative effects on the adsorption/immobilization capacity of clay minerals for heavy metals in contaminated soils.